Penerapan Model Cooperative Learning Tipe Student Teams Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Siswa - Dewi, Sulistiani; Rahayu, Puji; Nuraeni, Fitri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
The low student learning outcomes in mathematics may be caused by the selection of an inappropriate learning model. To be able to help students understand learning mathematics, it is necessary to take action that can improve learning outcomes. As an effort to improve student learning outcomes, this study used the STAD-type Cooperative Learning model with the type of Classroom Action Research (CAR). The purpose of this study is to determine the increase in student learning outcomes in mathematics before and after being given action in the form of applying the STAD-type Cooperative Learning model. Based on the findings that have been analyzed, there is an increase in learning outcomes in cycle I, namely during initial observations the average student learning outcomes in mathematics only amounted to 53.3. After the implementation of the first cycle of learning, student learning outcomes began to increase with an average value of 69.3. However, this increase tends to be still below the targeted completeness criteria. So earning was carried out again in cycle II. During the implementation of cycle II, it experienced an increase, namely an average value of 81.1 was obtained so that it could be declared